2015
DOI: 10.1111/jvs.12276
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem multifunctionality of coastal marshes is determined by key plant traits

Abstract: Questions As biodiversity losses increase due to global change and human‐induced habitat destruction, the relationships between plant traits and ecosystem properties can provide a new level of understanding ecosystem complexity. Using a functional response–effect approach, we show that multiple components of the carbon cycle are determined by a few plant traits, which in turn are strongly affected by environmental conditions. Location Salt marshes, northwest Germany. Methods We explored responses of morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 70 publications
(140 reference statements)
4
28
1
Order By: Relevance
“…The only field study showing a negative response of biomass production to increasing species richness was a study on plants in salt marshes (TREIBSEL, electronic supplementary material), where salinity and water regime, rather than nutrients, were the main drivers of diversity and biomass [36][37][38][39]. The limited ability of our model to explain variation in richness and realized productivity in salt marshes (only 8% for richness and 4% for realized productivity) seems to confirm that we did not quantify the key factors influencing this system.…”
Section: Discussionmentioning
confidence: 99%
“…The only field study showing a negative response of biomass production to increasing species richness was a study on plants in salt marshes (TREIBSEL, electronic supplementary material), where salinity and water regime, rather than nutrients, were the main drivers of diversity and biomass [36][37][38][39]. The limited ability of our model to explain variation in richness and realized productivity in salt marshes (only 8% for richness and 4% for realized productivity) seems to confirm that we did not quantify the key factors influencing this system.…”
Section: Discussionmentioning
confidence: 99%
“…Species composition and abundance were assessed by frequency analysis using a 1Â 1 m frame subdivided into 100 grids of 0.1Â 0.1 m. Nomenclature followed [34][35][36][37]. Further details of the study design for each project (except Comtess) can be found in [38] (Sequester), [22] (Treibsel) and [35,39] (Vista).…”
Section: Materials and Methods (A) Study Sites And Data Collectionmentioning
confidence: 99%
“…Such a mechanism was supported by the constancy of molecular C composition between Juncus biomass and litter ( Table 2). The selective resorption of N by a plant has important implications for the fate and processing of the resulting litter and residue, as tissue C : N is considered a primary determinant on salt marsh OM decomposition (Minden and Kleyer, 2015). By retaining nutrients within the living tissues, the plant effectively decreases the lability of resulting litter and residual soils and makes them less attractive to the microbial decomposer community (Hessen et al, 2013;Sterner and Hessen, 1994).…”
Section: Chemical Composition Of Deposits Varies Among Assemblagesmentioning
confidence: 99%
“…Together, these data from SE Australia contribute to a broader pattern of plant assemblage differences in salt marsh surface dynamics and C sequestration potential (Minden and Kleyer, 2015;Saintilan et al, 2013;Wang et al, 2003). They also highlight short-term processes that may contribute to the high capacity of Juncus salt marshes to accumulate significant C stocks globally (0.034 g C cm −2 yr −1 or 0.093 mg C cm −2 d −1 ), relative to most other salt marsh genera (mean C accumulation rate = 0.024 g C cm −2 yr −1 or 0.066 mg C cm −2 d −1 ; Ouyang and Lee, 2014).…”
Section: Chemical Composition Of Deposits Varies Among Assemblagesmentioning
confidence: 99%